2019
DOI: 10.1017/jog.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microparticles on deformation and microstructural evolution of fine-grained ice

Abstract: We investigated the effects of microparticles and grain size on the microstructural evolutions and mechanical properties of polycrystalline ice. Uniaxial compression tests were conducted using fine-grained pure ice and silica-dispersed ice under various conditions. Deformation behavior of fine-grained ice was found to be characterized by stress exponent n ≈ 2 and activation energy Q ≈ 60 kJ mol−1. The derived strain rates of fine-grained ice were ≈ 1 order of magnitude larger than those of coarse-grained ice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…At low equivalent stresses (< 1 MPa) and with the finest-grained samples, Goldsby and Kohlstedt found a third creep regime, which was again grain size independent but with n = 2.4. Recent studies (Saruya et al, 2019) have confirmed the occurrence of GSS creep in fine-grained ice, with n = 2 and p = 1.4. According to Goldsby and Kohlstedt, the GSI regime with n = 4 is governed by dislocation creep using the easy slip systems in ice (basal slip) rate-limited by the hard slip systems (i.e., nonbasal slip).…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…At low equivalent stresses (< 1 MPa) and with the finest-grained samples, Goldsby and Kohlstedt found a third creep regime, which was again grain size independent but with n = 2.4. Recent studies (Saruya et al, 2019) have confirmed the occurrence of GSS creep in fine-grained ice, with n = 2 and p = 1.4. According to Goldsby and Kohlstedt, the GSI regime with n = 4 is governed by dislocation creep using the easy slip systems in ice (basal slip) rate-limited by the hard slip systems (i.e., nonbasal slip).…”
Section: Introductionmentioning
confidence: 76%
“…The recent study by Saruya et al (2019) confirms the occurrence of GSS creep in fine-grained ice and proposes a different mechanism, where grain boundaries enhance creep by acting as sinks for dislocations. We emphasize that even though the exact mechanisms involved in GSS flow are not understood in detail, there is good experimental evidence for GSS creep in ice and the available flow laws provide a reasonable basis to investigate the role of these mechanisms in polar ice sheets.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations